The Influence of Donor and Recipient Gender Incompatibility on Corneal Transplant Rejection and Failure. Issue 1 (22nd July 2016) - Hopkinson, C. L.; Romano, V.; Kaye, R. A.; Steger, B.; Stewart, R. M. K.; Tsagkataki, M.; Jones, M. N. A.; Larkin, D. F. P.; Kaye, S. B.; ,
Abstract : In vascularized organ transplants, gender mismatches have higher rates of immunological rejection. We investigated the influence of gender incompatibility, including H‐Y incompatibility, on corneal transplant graft rejection and failure. Patients were included who had undergone a first corneal transplant for keratoconus (KC), Fuchs endothelial dystrophy (FED), pseudophakic bullous keratopathy (PBK), infection and other indications. A Cox regression model was fitted for each indication to determine factors affecting graft failure and rejection at 5 years. The impact of gender, including H‐Y, matching was analyzed after accounting for other factors, including known risk factors. Of 18 171 patients, 4314 had undergone a transplant for FED, 4783 for KC, 3669 for PBK, 1903 for infection and 3502 for other disorders. H‐Y mismatched (male [M]→female [F]) corneas were at greater risk of graft failure or rejection. For FED, F→F were 40% less likely to fail (p < 0.0001) and 30% less likely to reject (p = 0.01); M→M were 20% less likely to fail (p = 0.04) and 30% less likely to reject (p = 0.01). For KC, M→M matched corneas were 30% less likely to fail (p = 0.05) and 20% less likely to reject (p = 0.01) compared with H‐Y mismatches. H‐Y antigen mismatched (M→F) patients were at greater risk of rejection or graft failure. Abstract : The influence of gender incompatibility on graft rejection and survival following corneal transplantation in 18 171 patients shows H‐Y mismatched (M→F) transplants have a greater risk of graft failure or rejection, particularly in patients with Fuchs endothelial dystrophy and keratoconus.